2023
DOI: 10.32505/qalasadi.v7i1.5587
|View full text |Cite
|
Sign up to set email alerts
|

Eksplorasi Etnomatematika Konsep Transformasi Geometri Translasi pada Motif Kerajinan Manik-Manik Suku Dayak Kenyah

Abstract: This study aims to explore the Dayak Kenyah tribe's bead crafts through motifs  that found and relatedto geometry transformation’s concept. This kind research is the qualitative research thorough an ethnography approach. Data were collected through observation, interview and documentation. The subject of this research is bead crafts and the object of this research is the geometry transformation’s that found in the motifs of bead crafts’s made. The data obtained in this research came from derived from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The results of geometric transformations in the form of translations, rotations, reflections, and dilatations on Banyumasan batik are one of the local culture-based mathematical models that can be used as material for learning mathematics, making a positive contribution to the development of Indonesian art and culture through the integration of culture with the field of mathematics, especially the field of batik, as well as enrich insight and knowledge about the application of mathematics in everyday life. The study of Hafizh et al (2023) the concept of geometric translation was found in the bead crafts motifs of the Dayak Kenyah tribe which shows ethnomathematics in local culture. In the ethnomathematics study of Geulis Tasikmalaya Umbrella craftsmen, West Java the geometry of rotation and reflection was also found in the motifs drawn on umbrella crafts (Muslim & Prabawati, 2020).…”
Section: Rotationmentioning
confidence: 99%
“…The results of geometric transformations in the form of translations, rotations, reflections, and dilatations on Banyumasan batik are one of the local culture-based mathematical models that can be used as material for learning mathematics, making a positive contribution to the development of Indonesian art and culture through the integration of culture with the field of mathematics, especially the field of batik, as well as enrich insight and knowledge about the application of mathematics in everyday life. The study of Hafizh et al (2023) the concept of geometric translation was found in the bead crafts motifs of the Dayak Kenyah tribe which shows ethnomathematics in local culture. In the ethnomathematics study of Geulis Tasikmalaya Umbrella craftsmen, West Java the geometry of rotation and reflection was also found in the motifs drawn on umbrella crafts (Muslim & Prabawati, 2020).…”
Section: Rotationmentioning
confidence: 99%
“…Berbagai bentuk etnomatematika tersebut yang ditemukan berkaitan dengan konsep-konsep geometri pada matematika SD (konsep, segitiga, persegi panjang, belah ketupat, segi enam, lingkaran, balok, kerucut, dan tabung). Penelitian terkait etnomatematika lainnya juga telah banyak dilakukan, salah satunya yaitu eksplorasi konten transformasi geometri pada manik-manik suku Dayak Kenyah oleh (Haeruddin, et al, 2023) dan oleh (Yahya, et al, 2023) menunjukkan bahwa pada manik-manik suku Dayak Kenyah ditemukan konsep-konsep transformasi geometri yang meliputi translasi (pergeseran), refleksi (pencerminan), rotasi (perputaran), dan dilatasi (perkalian).…”
Section: Pendahuluanunclassified